Money Laundering and the Means to Combat it - Khater, Maya Hassan Mulla (Journal of Economic, Administrative and Legal Sciences, 2018)
Recently the Money Laundering is considered as one of the most famous economic crimes, because of its dangerous effects on the economics of different countries, and its threat to the stability of banking, finance and investment operations.Due to the great attention that given to combating the crime of Money Laundering, we will try in this research to focus on the efforts that confront it, at the international, regional, and national levels.In order to raise the awareness of all the relevant bodies that concerned with combating of money laundry, and to increase the efforts of all institutions which deal with this crime.
Keywords: money laundering crime; international law; international cooperation; international organizations; international agreements